Strengthening Student Character Through Internalization of Religious Values in School - Sofyan Sauri; Anwar Sanusi; Nalahuddin Saleh; Shofa Musthofa Khalid (IAIN Ambon, 2022)
Abstract: Religious character is the principal capital teachers must teach students in schools. The religious character formed from a religious footing will allow someone to measure everything. Therefore, strengthening religious character must be seen as a conscious and planned effort by the teacher, not an effort that occurs by chance. This study aimed to explore in depth the implementation of strengthening student character through the internalization of religious character values carried out by teachers in Cianjur district schools. This study uses a qualitative approach with a descriptive method. Furthermore, data collection is done through observation, interviews, and documentation. The results showed that the highest percentage of strengthening students' character through internalization of religious values carried out by teachers to students was the value of worship, as much as 95%. At the same time, the patient value has the lowest percentage, 75%. This shows that the value of patience must be increased again in its cultivation both in learning and outside the classroom. Abstrak: Karakter religius merupakan modal utama yang harus diajarkan oleh guru kepada siswa di sekolah. Karakter religius yang terbentuk dari pijakan religius akan memungkinkan seseorang untuk mengukur segala sesuatu. Oleh karena itu, penguatan karakter religius harus dilihat sebagai upaya sadar dan terencana oleh guru, bukan upaya yang terjadi secara kebetulan. Tujuan penelitian ini adalah untuk menggali secara mendalam tentang pelaksanaan penguatan karakter siswa melalui internalisasi nilai-nilai karakter religius yang dilakukan oleh guru di sekolah kabupaten Cianjur. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Selanjutnya pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa persentase paling tinggi dari penguatan karakter siswa melalui internalisasi nilai-nilai religius yang dilakukan oleh guru kepada siswa adalah nilai ibadah sebanyak 95%. Sedangkan nilai sabar memiliki persentase paling rendah yaitu 75%. Hal ini menunjukkan bahwa nilai sabar mesti ditingkatkan kembali dalam penanamannya baik dalam pembelajaran di kelas maupun di luar kelas.